THE ROLE OF NISIN, POTASSIUM SORBATE AND SODIUM LACTATE AS ADDITIVE IN IMPROVING THE CHEMICAL AND QUALITATIVE CHARACTERISTICS OF CHILLED GROUND BEEF. - Narjis S. A. Mula,; Alrubeii A. M. S., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to evaluate the effects of nisin, potassium sorbate and sodium lactate and their interactions as preservatives in fat oxidation, some quality and microbial characteristics of chilled ground beef meat stored at 4C˚ for 0,4,8 and 12 days. The study included nine different treatments: T1 (control treatment without addition), T2 (nisin at a concentration of 150 mg/kg), T3 (potassium sorbate 0.075 g/kg), T4 (sodium lactate 3%), T5 (nisin 150 mg/kg + potassium sorbate 0.075 g/kg), T6 (nisin 150 mg/kg + sodium lactate 3%), T7 (Sodium Lactate 3% + Potassium Sorbate 0.075 g/kg), T8 (Nisin 150 mg/kg + Sodium Lactate 3% + Potassium Sorbate 0.075 g/kg) and T9 (Addition of Butylated hydroxyanisole(BHA 0.01%)). All treatments showed significant (p